Impact of DHCWs' Safety Perception on Vaccine Acceptance and Adoption of Risk Mitigation Strategies. (April 2023) - Coker, M.O.; Subramanian, G.; Davidow, A.; Fredericks-Younger, J.; Gennaro, M.L.; Fine, D.H.; Feldman, C.A.
Objectives: To estimate the association between safety perception on vaccine acceptance and adoptions of risk mitigation strategies among dental health care workers (DHCWs). Methods: A survey was emailed to DHCWs in the New Jersey area from December 2020 to January 2021. Perceived safety from regular SARS-CoV-2 testing of self, coworkers, and patients and its association with vaccine hesitancy and risk mitigation were ascertained. Risk Mitigation Strategy (RiMS) scores were computed from groupings of office measures: 1) physical distancing (reduced occupancy, traffic flow, donning of masks, minimal room crowding), 2) personal protective equipment (fitted for N95; donning N95 masks; use of face shields; coverings for head, body, and feet), and 3) environmental disinfection (suction, air filtration, ultraviolet, surface wiping). Results: SARS-CoV-2 testing of dental professionals, coworkers, and patients were perceived to provide safety at 49%, 55%, and 68%, respectively. While dentists were least likely to feel safe with regular self-testing for SARS-CoV-2 (P < 0.001) as compared with hygienists and assistants, they were more willing than hygienists (P = 0.004; odds ratio, 1.79 [95% CI, 1.21 to 2.66]) and assistants (P < 0.001; odds ratio, 3.32 [95% CI, 1.93 to 5.71]) to receive the vaccine. RiMS scores ranged from 0 to 19 for 467 participants (mean [SD], 10.9 [2.9]). RiMS scores did not significantly differ among groups of DHCWs; however, mean RiMS scores were higher among those who received or planned to receive the COVID-19 vaccine than those with who did not (P = 0.004). DHCWs who felt safer with regular testing had greater RiMS scores than those who did not (11.0 vs. 10.3, P = 0.01). Conclusions: Understanding DHCWs' perception of risk and safety is crucial, as it likely influences attitudes toward testing and implementation of office risk mitigation policies. Clinical studies that correlate risk perception and RiMS with SARS-CoV-2 testing are needed to demonstrate the effectiveness of RiMS in dental care settings. Knowledge Transfer Statement: Educators, clinicians, and policy makers can use the results of this study when improving attitudes toward testing and implementation of risk mitigation policies within dental offices, for current and future pandemics.